Double narrative of a researcher and the researched: the journey of English-language learning. Issue 3 (3rd May 2016) - Tsedendamba, Nara
Abstract: As I embarked on my PhD study in Australia, I felt excited because my study was born out of reflection on my own journey of English-language learning. I decided to use my experiences as a touchstone for an understanding of the experiences of others like me. The study presented here is part of a larger study and is a double narrative that explores the researcher's and the four participants' experiences of learning English language in their home country contexts and also in Australia while they are studying in an Australian tertiary context. Through a reflective practice, I have reflectively studied my and the participants' experiences with language learning strategies (LLS) to improve English-language skills and to better socialise into Australian academic and social discourses as international students. By linking the researcher and the researched closely, this research makes a contribution to English learning and teaching on the development of English-language skills of international students through the use of LLS. It provides some implications to institutions and advice to students like me.